Stenotrophomonas maltophilia: an unusual pathogen for pneumonia in an immunocompetent patient - Manappallil, Robin George; Sabir, Mele Chelakkoth (Asian Journal of Medical Sciences, 2017)
No abstract Asian Journal of Medical Sciences Vol.8(6) 2017 47-48